Les fonctions sphériques et quelques applications - KAIDAR, Dalal; SAYADI, Sara; ZEGHOUD, Khaoula (university of eloued جامعة الوادي, 2015)
في هره انمركسة قدمنا اندوال انكسويت, بعط أصنافها و خصائصها انمميزة و وظحنا مدي أهميخها كخطبيقاث في انمسائم انفيزيائيت و كرا انمسائم انسياظيت انفيزيائيت , و ذنك نغسض نفج الانخباه نها باعخبازها صنفا هاما من اندوال انخاصت انخي حعخبس مفخاحا نخطىز مخخهف انعهىو, و أيعا من اجم حسهيط انعىء عهيها في مجالاث أوسع بهدف اكخشاف آفاق جديدة.In this memory we represented the spherical functions , some of their types and properties, then we clarified the importance of these functions as applications in physical mathematic problems to bend the attention to it since it represents an important class of special functions in order to use it in different domains to discover new applications in new horizons.
mémoire licence matimatuque